The Role of Scientific Literacy in Climate Change-Based Science Learning: A Literature Review - Gesti Maharani; Melani Aulia Hatami (Indonesian Publication Center, 2025)
This study aims to examine the strengthening of students’ scientific literacy through science learning that integrates climate change issues. The method employed was a narrative literature review by analyzing national and international articles published between 2019 and 2025 that are relevant to scientific literacy, science education, and issue-based learning approaches. The findings indicate that the integration of climate change issues, particularly through the Socio-Scientific Issues (SSI) approach, enhances conceptual understanding, data analysis skills, scientific argumentation, and evidence-based decision-making. Learning innovations such as climate flashcards, science gardens, digital modules, and the use of AR/VR technologies contribute to increased student engagement and data literacy. Overall, issue-based science learning that incorporates climate change has proven effective in developing students’ scientific literacy and environmental awareness. This review recommends the development of more contextual and sustainability-oriented learning strategies.